The Transnational Beginnings of Children’s Rights (First Third of the 20th Century) - Joana Miguelena Torrado; Pauli Dávila Balsera; Luis M. Naya Garmendia (Espacio, Tiempo y Educación, 2021)
The international recognition of children’s rights began in 1924 within the framework of the League of Nations, with the so-called Geneva Declaration. The aim of this article is to analyse the root causes that made this declaration possible, focusing on a set of international conferences that addressed the topic of child protection, as well as on the charters and declarations on the rights of the child and on the Geneva Declaration itself, which we analyse using content analysis. The main sources are three lesser-known documents: the Moscow Declaration, the Korczak Declaration, and a publication in which children drew pictures to illustrate their understanding of their rights. The primary conclusion is that at the beginning of the 20th century these activities and meetings, in addition to the texts defending children’s rights, and national protection policies and institutions, contributed to international recognition of the rights of children and adolescents, which, until that moment, had been only vaguely defined and lacked a solid legal framework. In this sense, there was a transnational phenomenon that moved from protecting children to recognising their rights, which were enshrined in the subsequent international treaties published throughout the 20th century, culminating in the 1989 Convention on the Rights of the Child.